2008
DOI: 10.1007/s10342-008-0221-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient contents and efficiencies of beech and spruce saplings as influenced by competition and O3/CO2 regime

Abstract: Saplings of Fagus sylvatica and Picea abieswere grown under conditions of intra and interspeciWc competition in a 2-year phytotron study under combinations of ambient and elevated ozone (+O 3 which is 2 £ O 3 , but <150 nl l ¡1 ) as well as carbon dioxide concentrations (+CO 2 which is amb. CO 2 + 300 l CO 2 l ¡1 ) in a full factorial design. Saplings were analysed for various mineral nutrients in diVerent plant organs as well as biomass production and crown development. The study was based on the assumption t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“… spruce tree No 350 Pfirrmann et al, 1996 Picea abies 'Karst.' spruce tree No 300 Rodenkirchen et al, 2009 Picea abies 'Karst.' spruce tree No 300 Weigt et al, 2011 Picea rubens spruce tree No 350 Shipley et al, 1992 Pinus ponderosa pine tree No 346 USA Walker et al, 2000 Pinus ponderosa 'Laws.'…”
Section: Methodsmentioning
confidence: 99%
“… spruce tree No 350 Pfirrmann et al, 1996 Picea abies 'Karst.' spruce tree No 300 Rodenkirchen et al, 2009 Picea abies 'Karst.' spruce tree No 300 Weigt et al, 2011 Picea rubens spruce tree No 350 Shipley et al, 1992 Pinus ponderosa pine tree No 346 USA Walker et al, 2000 Pinus ponderosa 'Laws.'…”
Section: Methodsmentioning
confidence: 99%
“…Under conditions of interspecific competition, P. abies was found to be superior in nitrogen acquisition whereas F. sylvatica in turn appeared to be nitrogen-limited (Grams and Matyssek 2010;Kozovits et al 2005). Effects on nutrient efficiency indicate that processes of stress defence due to O 3 exposure trigger a nutrient demand at the expense of above-ground competition (Rodenkirchen et al 2009). Recently, Grams et al (2012) demonstrated that the more intense the competition between F. sylvatica and P. abies is, the stronger the response to other stressors may be modified.…”
Section: Plant Competition and Community Compositionmentioning
confidence: 95%
“…For estimating the dry matter production of the saplings, a reference dry weight of ten randomly chosen saplings was obtained at the first day of the study. Biomass production was calculated as the difference in dry weight at the beginning and at the end of the study by subtracting the mean initial dry weight of the reference plants from the plant's weight at harvest (Cernusak et al 2009, Rodenkirchen et al 2009). …”
Section: Determination Of Growth-related Parametersmentioning
confidence: 99%